Kematangan Emosi, Problem-Focused Coping, Emotion-Focused Coping dan Kecenderungan Depresi pada Mahasiswa Tahun Pertama - Amalia Nur Aisyah Tuasikal; Sofia Retnowati (Gadjah Mada Journal of Psychology (GamaJoP), 2018)
This research aimed to examine the relationship between emotional maturity, problem-focused coping, emotion-focused coping and depression among first-year college students. It was hypothesized that emotional maturity, problem-focused coping, and emotion-focused coping correlate with the tendency of depression among first-year college students. Participants were 214 college students in Yogyakarta (male=66; female=148). Multiple regression analysis showed that emotional maturity and emotion-focused coping contribute significantly to first-year college students depression with 19% contribution (R² = 0.19; p < 0.05). Emotional maturity negatively correlated with depression tendency (t = -6.026; p < 0.05), while emotion-focused coping positively correlated with first-year college students depression tendency (t = 2.265; p < 0.05). Result showed that problem-focused coping has no significant relationship with depression tendency (t = -0.557; p > 0.05).